The association between multimorbidity and needs-based quality of life in primary care: a cross-sectional questionnaire study - Clara Valgaard Jørgensen; Henrik Hedegaard Pliess Larsen; Volkert Siersma; Anne Holm (Scandinavian Journal of Primary Health Care)
Introduction A negative association between the number of chronic conditions and quality of life (QoL) is well known, butthe complexity of this association is not fully understood. This study aimed to 1) examine the association between the number of diagnosis groups, as a measure of multimorbidity, and needs-based QoL, and 2) explore how this association varies across sociodemographic subgroups.Methods This cross-sectional study included adults with chronic conditions managed at a general practitioner (GP) who participated in a cluster-randomized trial. The exposure was the number of self-reported diagnosis groups, using an organ-specific definition, and the outcome was needs-based QoL measured using the Multi Morbidity Questionnaire 1 (MMQ1). Multivariable linear regression models were used, and a Minimal Important Difference (MID) for each domain were calculated to assess the clinical relevance.Results The study included 31,753 patients. Significant, linear, associations were found between the number of diagnosis groups and needs-based QoL. Age, education, occupation, and living alone were identified as effect modifiers. The strongest associations were observed among participants aged 40–59 years, those with lower educational levels, the unemployed, and those living alone.Conclusion A cumulative burden of multimorbidity was identified as increasing number of diagnoses was associated with lower needs-based QoL. Socioeconomically and socially vulnerable groups may experience greater impacts on their QoL and may benefit from additional support or more personalized care approaches. These findings highlight the importance of a bio-psycho-social approach when caring for patients with chronic disease and multimorbidity in general practice.